2023
DOI: 10.1038/s41467-023-40778-w
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear receptor HR96-related gene underlies large trans-driven differences in detoxification gene expression in a generalist herbivore

Meiyuan Ji,
Marilou Vandenhole,
Berdien De Beer
et al.

Abstract: The role, magnitude, and molecular nature of trans-driven expression variation underlying the upregulation of detoxification genes in pesticide resistant arthropod populations has remained enigmatic. In this study, we performed expression quantitative trait locus (eQTL) mapping (n = 458) between a pesticide resistant and a susceptible strain of the generalist herbivore and crop pest Tetranychus urticae. We found that a single trans eQTL hotspot controlled large differences in the expression of a subset of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…In the F2 backcross approach, we found evidence for the dominant inheritance of performance on tomato (Figure 5B). Natural variation in the expression of genes involved in allelochemical detoxification is often trans-regulated and inherited as a dominant trait in this species, and thus is open for selection when it is exposed in heterozygous diploid females (Ji et al, 2023;Kurlovs et al, 2022).…”
Section: Selection From Tomato Yields High Performing Individualsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the F2 backcross approach, we found evidence for the dominant inheritance of performance on tomato (Figure 5B). Natural variation in the expression of genes involved in allelochemical detoxification is often trans-regulated and inherited as a dominant trait in this species, and thus is open for selection when it is exposed in heterozygous diploid females (Ji et al, 2023;Kurlovs et al, 2022).…”
Section: Selection From Tomato Yields High Performing Individualsmentioning
confidence: 99%
“…In contrast, generalists exploit a wide range of hosts, requiring flexibility in their mechanisms of host use (Grbić et al, 2011). Plasticity in the molecular mechanisms that regulate genes involved in host use can enable generalists to cope with multiple classes of phytochemicals (Ji et al, 2023;Pym et al, 2019;Snoeck et al, 2018;Vandenhole et al, 2021). While generalists and specialists largely employ similar, but not identical mechanisms to exploit their hosts (Ali & Agrawal, 2012;Bruinsma et al, 2023;Bui et al, 2018), it is not well understood how selection shapes the diversity of mechanisms involved in host use in generalists, or whether genetic changes due to selection impact the host range of locally adapted populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 10 ) were the first ones to show, in vitro , the ability of these enzymes to glycosylate a broad range of plant secondary metabolites and acaricides, indicating that these UGTs play a role in mite host and pesticide adaptations. A recent eQTL study revealed that the over-expression of at least some UGTs is coregulated with other detoxifying enzymes such as cytochrome P450s, by a master regulator from the HR96 hormone receptor family, reinforcing their role in adaptation and resistance ( 23 ).…”
mentioning
confidence: 99%
“…It is assumed that specific properties of flavonoids arise from their molecular structure, such as the presence or absence of functional groups, as well as conjugated groups, like sugar moieties ( 29 , 30 , 31 ). For example, different flavonoids and their glycoside derivatives possess different anti-herbivore and anti-cancer attributes ( 23 , 32 ). Consistently, it has been shown that bacteria and herbivores rely on UGTs to detoxify these compounds ( 10 , 33 , 34 ).…”
mentioning
confidence: 99%